Complexity of approximate query answering under inconsistency in datalog+/- - Lukasiewicz, T; Malizia, E; Molinaro, C (CEUR Workshop Proceedings, 2018)
Several semantics have been proposed to query inconsistent ontological knowledge bases, including the intersection of repairs and the intersection of closed repairs as two approximate inconsistency-tolerant semantics. In this paper, we analyze the complexity of conjunctive query answering under these two semantics for a wide range of Datalog+/- languages. We consider both the standard setting, where errors may only be in the database, and the generalized setting, where also the rules of a Datalog+/- knowledge base may be erroneous.